EFFECT OF THE PLASTIC COVER COLOR AND ELECTROCUTION IN ROOT GROWTH INDICATORS AND VOLATILE OILS CONTENT OF THE TANACETUIM PARTHENIUM L.OF PLANT ROOTS - Z. J. Al-Mousawi; S.O.Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was carried out in the scientific experiments field of the Faculty of Agriculture - University of Baghdad, during the agricultural season 2015-2016 to study the effect of the plastic cover color and electrocution in root growth indicators and the volatile oils content of the roots, the research was done according to the randomized complete block design (RCBD) within .Split plot design. The first factors .(Main plot)was the plastic cover color (transparent, yellow, red and blue) and the second factor (Sub plot. incorporates four levels of stressed electrocution (0,2,4, 6 Amp) for 4 minutes, thereby resulting 48 experimental units (4 × 4 × 3) as the experimental unit contains 10 plants. The differences amonge means were tested using LSD at a level of probability of 0.05. The results showed superiority of the plants growing under a yellow cover (Y) in the root growth indicators, which included root length and surface area of ​​the roots and weight mild and dry (20.41 cm and 0.943 dcm2 and 111.1 g and 47.32 g) and the content of the roots of the volatile oils, which included Camphor ,Camphene and P-Cymene (5.514 µg.g-1 and 1.317 µg.g-1 and 0.693 µg.g-1) and the superiority of electric shock treatment level (4Amp) a significant increase in root growth indicators and the content of the roots of the volatile oils (25.58 cm and 90.09 g and 143.99 and 56.73 and 1.466 µg.g-1and 0.782 µg.g-1and 0.380 µg.g-1), respectively, resulted in the treatment of overlap between the color of the cover electric stun significant effect on root growth indicators and the content of the roots of the volatile oils, it outperformed the treatment of overlap (YA2) a significant increase in root surface area of ​​the roots of the length, weight mild, dry weight and content of the roots of Camphor and Camphene and P-Cymene (27.00 cm and 1.426 dcm 2 and 160.32 g 72.59 g and 2.998 µg.g-1 and 2.100 µg.g-1 and 0.895 µg.g-1), respectively. It can be conclude that of the plastic cover color and electric shocks had significant effect on growth and stimulate the prodaction of volatile oils in plant roots.